FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT - Heryanto, Heru; Laela, Nur; Dewi, Riana R (eBA Journal: Journal Economics, Bussines and Accounting, 2019)
This study aims to determine the significance of the influence of competence, independence, professionalism, auditor experience, accountability, and auditor's knowledge of audit quality. This study uses a questionnaire with a population and sample, namely all auditors who work at the Public Accounting Office (KAP) in the Special Region of Yogyakarta and Surakarta. Sampling techniques using Convenience Sampling with a sample of 61 respondents. The data used in this study is a questionnaire using a Likert scale 1 to 5. The data analysis technique used in this study is multiple linear regression using the SPSSprogram for Windows. The analysis tool in this study using validity and reliability, the classical assumption (normality test, multicollinearity, heteroscedasticity test and autocorrelation test) while the data were analyzed using multiple linear regression test, t test, F test and the coefficient of determination (R2).Based on the results of the t-test analysis performed, it shows that there is a positive influence of competence, independence, professionalism, auditor experience, accountability, and auditor's knowledge of audit quality and simultaneously competency, independence, professionalism, auditor experience, accountability, and auditor knowledge variables affect quality audit